Joint position sense testing at the wrist and its correlations with kinesiophobia and pain intensity in individuals who have sustained a distal radius fracture: A cross-sectional study. - Cantero-Téllez, Raquel; Algar, Lori A.; Cruz Gambero, Leire; Villafañe, Jorge Hugo; Naughton, Nancy (Elsevier, 2024)
Background: Sensorimotor impairment following distal radius fracture (DRF) has been associated with a significant decline in function. Joint position sense (JPS) testing is a meaningful and responsive way to assess sensorimotor impairment for individuals who have sustained a DRF; however, there are factors that may influence the results of JPS testing, including kinesiophobia and pain intensity. Purpose: This study aimed to evaluate the influence kinesiophobia may have on wrist JPS testing and if pain intensity impacts kinesiophobia and JPS in individuals with a DRF. Study Design: This was a cross-sectional study. Methods: Participants referred from two medical centers with a diagnosis of DRF treated with at least 3 weeks of immobilization were enrolled in the study. Data were collected at 1 week and 6 weeks postimmobilization period. Demographics were summarized with descriptive statistics, and linear relationships between kinesiophobia, pain intensity, and wrist JPS were examined using Pearson correlation coefficient. Results: Forty-eight participants were included in this study (mean age 42.9 years). Significant positive correlations were found between the Tampa Scale for Kinesiophobia (TSK) and Numeric Rating Scale (NRS; r = 0.951, p < 0.001), TSK and JPS error (r = 0.942, p < 0.001), as well as NRS and JPS error (r = 0.898, p < 0.001). These correlations indicate that higher levels of kinesiophobia are associated with increased pain intensity and greater JPS error. T-tests reveal no significant difference between male and female for the TSK, NRS, or JPS scores. Conclusions: There is an association for individuals with high levels of kinesiophobia and both greater pain and errors with JPS testing
Keywords: Mano - Enfermedades - Fisioterapia; Muñecas (Anatomía) - Lesiones y heridas; Joint position sense test; Kinesiophobia; Distal radius fracture; Pain